Effects of irrigation and nitrogen application on soil water and nitrogen distribution and water-nitrogen utilization of wolfberry in the Yellow River Irrigation Region of Gansu Province, China - Rongrong Tian; Guangping Qi; Yanxia Kang; Qiong Jia; Jinghai Wang; Feng Xiao; Yalin Gao; Chen Wang; Qiang Lu; Qidong Chen (Frontiers in Plant Science, 2023)
To address the problems of extensive field management, low productivity, and inefficient water and fertilizer utilization in wolfberry (Lycium barbarum L.) production, an appropriate water and nitrogen regulation model was explored to promote the healthy and sustainable development of the wolfberry industry. Based on a field experiment conducted from 2021 to 2022, this study compared and analyzed the effects of four irrigation levels [75%–85% θf (W0, full irrigation), 65%–75% θf (W1, slight water deficit), 55%–65% θf (W2, moderate water deficit), and 45%–55% θf (W3, severe water deficit)] and four nitrogen application levels [0 kg·ha−1 (N0, no nitrogen application), 150 kg·ha−1 (N1, low nitrogen application), 300 kg·ha−1 (N2, medium nitrogen application), and 450 kg·ha−1 (N3, high nitrogen application)] on soil water distribution, soil nitrate nitrogen (NO3−–N) migration, yield, and water-nitrogen use efficiency of wolfberry. The soil moisture content of the 40–80 cm soil layer was higher than those of 0-40 cm and 80-120 cm soil layer. The average soil moisture content followed the order of W0 > W1 > W2 > W3 and N3 > N2 > N1 > N0. The NO3−–N content in the 0–80 cm soil layer was more sensitive to water and nitrogen regulation, and the cumulative amount of NO3−–N in the soil followed the order of W0 > W1> W2 > W3 and N3 > N2 > N1 > N0 during the vegetative growth period. There was no evidently change in soil NO3−–N accumulation between different treatments during the autumn fruit. The yield of wolfberry under the W1N2 treatment was the highest (2623.09 kg·ha−1), which was 18.04% higher than that under the W0N3 treatment. The average water consumption during each growth period of wolfberry was the highest during the full flowering period, followed by the vegetative growth and full fruit periods, and the lowest during the autumn fruit period. The water use efficiency reached a peak value of 6.83 kg·ha−1·mm−1 under the W1N2 treatment. The nitrogen uptake of fruit and nitrogen fertilizer recovery efficiency of fruit first increased and then decreased with increasing irrigation and nitrogen application. The treatment of W1N2 obtained the highest nitrogen uptake of fruit and nitrogen recovery efficiency of fruit, which were 63.56 kg·ha−1 and 8.17%, respectively. Regression analysis showed that the yield and water-nitrogen use efficiency of wolfberry improved when the irrigation amount ranged from 315.4 to 374.3 mm, combined with nitrogen application amounts of 300.0 to 308.3 kg·ha−1. Additionally, the soil NO3−–N residue was reduced, making it an optimal water and nitrogen management model for wolfberry planting. The present findings contribute novel insights into the production of wolfberry with saving water and reducing nitrogen, which helps to improve the level of wolfberry productivity in the Yellow River irrigation region of Gansu Province and other areas with similar climate.